Simulation of Electric Field Distribution on Meniscus of Electrospray with Zinc Oxide Material - Andam Deatama Refino; Hadi Teguh Yudistira; Denny Hidayat Tri Nugroho; Deska Lismawenning (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM), Institut Teknologi Sumatera, Lampung Selatan, Lampung, Indonesia, 2019)
Electrospray system had attracted attention of many researchers. It is due to easy to yield uniform thin film and possible for thin film mass production. The important parameters of electrospray process for getting uniform thin film are electric field distribution, surface substrate treatment and solvent properties. In this work, we observed electric field distribution on meniscus. Numerical work has carried out on this work. The material on meniscus used zinc oxide liquid properties. Voltage and walking distance between nozzle and substrate are the most important parameter to adjust electric field distribution. The decreasing walking distance with constant voltage yields increasing electric field distribution on meniscus. On vice versa, the increasing walking distance yields decreasing electric field distribution on meniscus. Increasing and decreasing voltage yields increasing and decreasing electric field distribution on meniscus, respectively.